Organocatalytic, Chemoselective, and Stereospecific House-Meinwald Rearrangement of Trisubstituted Epoxides - Dressler, Friedemann; Justus Liebig University Giessen (My University, 2023)
We present a novel method for the chemoselective House-Meinwald rearrangement of trisubstituted epoxides under mild conditions with the use of simple perfluorinated disulfonimides as Brønsted acid catalysts. We isolated the α-quaternary aldehyde products in yields of 27-97% using catalyst loadings as low as 0.5 mol% on a scale of 1 mmol. In addition, we show the stereospecific rearrangement using an enantioenriched substrate, which makes this method suitable for applications in total synthesis of natural products. We provide free induction decay (FID) of nuclear magnetic resonance (NMR) spectra of new compounds obtained within the manuscript submitted for publication in Synlet (Thieme). The NMR spectra were recorded on Bruker AV 400 or AV 400HD spectrometers at 298 K (400 MHz for 1H NMR, 377 MHz for 19F NMR, and 101 MHz for 13C NMR). To open and read the FID files either use the programs "Mnova" (https://mestrelab.com/download/mnova/) or "Bruker TopSpin" (https://www.bruker.com/en/products-and-solutions/mr/nmr-software/topspin.html).
Keywords: ddc:540